2021
DOI: 10.3390/cancers13112647
|View full text |Cite
|
Sign up to set email alerts
|

Right and Left Colorectal Cancer: Differences in Post-Surgical-Care Outcomes and Survival in Elderly Patients

Abstract: (1) There is evidence of the embryological, anatomical, histological, genetic and immunological differences between right colon cancer (RCC) and left colon cancer (LCC). This research has the general objective of studying the differences in outcome between RCC and LCC. (2) A longitudinal analytical study with prospective follow-up of the case–control type was conducted from 1 January 2010 to 31 December 2017 including 398 patients with 1:1 matching, depending on the location of the tumor. Inclusion criteria: p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Multiple studies have suggested that the PTL influenced the prognosis of patients with advanced CRC, and patients with left-sided colon cancer (L-CC) had a better OS compared with that of patients with R-CCs (26)(27)(28). However, whether PTL was associated with long-term survival in patients with CRC liver metastases after radical resection of the primary tumor and metastatic tumor remains inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have suggested that the PTL influenced the prognosis of patients with advanced CRC, and patients with left-sided colon cancer (L-CC) had a better OS compared with that of patients with R-CCs (26)(27)(28). However, whether PTL was associated with long-term survival in patients with CRC liver metastases after radical resection of the primary tumor and metastatic tumor remains inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with LCC benefit more from chemotherapy and targeted therapy and also experienced a better prognosis, while patients with RCC showed more promising results in immunotherapy 29 . Mirón Fernández et al 30 pointed out that there were significant differences between RCC and LCC in terms of evolution, progression, complications, and survival. Compared with LCC, RCC had a more advanced N stage, a larger tumor volume, lower tumor differentiation, and a higher positive rate of lymphatic vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with left-sided CRC (LCRC), right-sided CRC (RCRC) is usually associated with poor prognosis, and also presents more advanced N stage, larger tumor size, poorly differentiated tumors, as well as higher probability of lymphatic vascular invasion ( 48 ). In addition, RCRC also presented higher hypermethylation and higher microsatellite instability (MSI) frequency than LRCR ( 26 , 49 ).…”
Section: Discussionmentioning
confidence: 99%